MILLENNIAL INVESTOR DECISION ANALYSIS AND ITS DETERMINANTS (AN ENDOGENEITY PERSPECTIVE) - Abel Tasman; Fajri Adrianto; Mohamad Fany Alfarisi; Masyhuri Hamidi; Fajri Muharja (Jurnal Apresiasi Ekonomi, 2023)
This study aims to see 1) The effect of Financial Literacy on the investment decisions of the millennial generation in Padang City 2) The effect of Risk Perception on the investment decisions of the millennial generation in Padang City 3) This type of research is a comparative causal research (Causative). The sample in this study was 96 respondents who are the Millennial generation of Padang City with a purposive sampling method. The types of data in this study are primary data and secondary data. This study uses panel data regression analysis. The data collection technique used is a questionnaire. Instrument trials use validity and reliability tests. Prerequisite analysis tests carried out included normality tests, heteroscedasticity tests, and multicollinearity tests. The collected data was analyzed using SPSS version 20.0. This study also examines endogeneity by using financial literacy as an endogenous variable and risk perception as an instrument variable. The results of this study indicate 1) Financial Literacy has a significant positive effect on the investment decisions of the millennial generation in Padang City 2) Risk Perception has a positive but not significant effect on the investment decisions of the millennial generation in Padang City due to endogeneity